Finding Alphas, 2nd Edition - Tulchinsky, Igor (Wiley, 2019)
Discover the ins and outs of designing predictive trading models Drawing on the expertise of WorldQuant's global network, this new edition of Finding Alphas: A Quantitative Approach to Building Trading Strategies contains significant changes and updates to the original material, with new and updated data and examples. Nine chapters have been added about alphas - models used to make predictions regarding the prices of financial instruments. The new chapters cover topics including alpha correlation, controlling biases, exchange-traded funds, event-driven investing, index alphas, intraday data in alpha research, intraday trading, machine learning, and the triple axis plan for identifying alphas." Provides more references to the academic literature " Includes new, high-quality material " Organizes content in a practical and easy-to-follow manner " Adds new alpha examples with formulas and explanations If you're looking for the latest information on building trading strategies from a quantitative approach, this book has you covered